Bi‐Based Metal‐Organic Framework Derived Leafy Bismuth Nanosheets for Carbon Dioxide Electroreduction. Issue 36 (2nd August 2020) - Yang, Jian; Wang, Xiaolin; Qu, Yunteng; Wang, Xin; Huo, Hang; Fan, Qikui; Wang, Jin; Yang, Li‐Ming; Wu, Yuen
Abstract: Electroreduction of carbon dioxide (CO2 ) into high‐value and readily collectable liquid products is vital but remains a substantial challenge due to the lack of highly efficient and robust electrocatalysts. Herein, Bi‐based metal‐organic framework (CAU‐17) derived leafy bismuth nanosheets with a hybrid Bi/BiO interface (Bi NSs) is developed, which enables CO2 reduction to formic acid (HCOOH) with high activity, selectivity, and stability. Specially, the flow cell configuration is employed to eliminate the diffusion effect of CO2 molecules and simultaneously achieve considerable current density (200 mA cm −2 ) for industrial application. The faradaic efficiency for transforming CO2 to HCOOH can achieve over 85 or 90% in 1 m KHCO3 or KOH for at least 10 h despite a current density that exceeds 200 mA cm −2, outperforming most of the reported CO2 electroreduction catalysts. The hybrid Bi/BiO surface of leafy bismuth nanosheets boosts the adsorption of CO2 and protects the surface structure of the as‐prepared leafy bismuth nanosheets, which benefits its activity and stability for CO2 electroreduction. This work shows that modifying electrocatalysts by surface oxygen groups is a promising pathway to regulate the activity and stability for selective CO2 reduction to HCOOH. Abstract : Herein, leafy bismuth nanosheets are shown to achieve CO2 electroreduction to HCOOH with high activity (>200 mA cm −2 ), selectivity (>90%) and stability (>10 h) by employing in gas diffusion cell configuration. According to the in‐depth characterizations, the large electrochemically accessible surface area and the superficial BiO species for Bi nanosheets are the key factors that enable the high catalytic activity.